Antibiotic Demand in the Presence of Antimicrobial Resistance - Dubois, Pierre; Gökkoca, Gökçe (The Review of Economics and Statistics, 2025)
Abstract Antimicrobial resistance (AMR) increases healthcare costs, hospital stays, and mortality. This study examines how AMR affects antibiotic prescribing for cystitis in France (2002–2019), using data from general practitioners. A decision model is developed to capture prescribing behavior with and without rapid bacterial or susceptibility testing. To address endogeneity, veterinary antibiotic sales are used as instruments. Results show rising resistance prompts drug substitution, and physicians respond to predictable resistance trends. Counterfactual analysis reveals that reducing animal antibiotic use and limiting fluoroquinolones lowers resistance but affects substitution and consumer welfare differently. The study also assesses the value of rapid diagnostic testing.